Sexual Assault: What do Perinatal Nurses Need to Know?. Issue 5 (September 2019) - Wisner, Kirsten
Abstract : Many women in the United States have experienced sexual violence. In a recent survey, nearly half of women have reported some type of contact sexual violence in their lifetime, and approximately one in five women reported an attempted or completed rape. Our maternity nursing expert, Dr. Wisner, offers advice on how to support women who have experienced sexual assault using trauma-informed care.